SCENES OF ENCOUNTER IN LAILA LALAMI’S THE MOOR’S ACCOUNT - Amal BATTACHE, Bouchra BOUHALI (My University, 2021)
Laila Lalami has been known for narrating stories of marginalized people and alienated cultures. In her novel, The Moor’s Account (2014), she protests Eurocentrism and attempts to restore the cultural heritage of marginalized people. The present study examines cross-cultural encounters in the novel through Homi Bhabha’s theories of hybridity, mimicry, ambivalence, and unhomeliness. It investigates the cultural differences, clashes, and interactions between the colonizer and the colonized, highlighting the significance of storytelling in the life of the main character Mustafa and in the life of other characters. Moreover, the study emphasises the importance of names and naming as identity markers in the colonial and postcolonial world. Thus, the study is divided into two chapters. The first chapter presents the socio-historical context and the theoretical framework. The second chapter, on the other hand, analyses the main character’s identity (de)formation in the light of Bhabha’s theories.
Keywords: Keywords: cultural encounters, postcolonialism, naming, hybridity, mimicry, unhomeliness